Causal Relationship Between Islamic Bonds, Oil Price and Precious Metals: Evidence From Asia Pacific - Widad, Metadjer; Hadjer, Boulila (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Sukuk or Islamic bonds as new “Halal” securities had wildly expanded in Muslim and non-Muslim capital markets. So, this study aims to investigate the causal relationship between Islamic bonds (sukuk), oil and precious metals “silver and gold” prices in Asia pacific. This study used VAR model relying on daily data. The findings of Granger causality test and impulse-responses analysis results provide substantial evidence in favor of the relation between sukuk and the commodity market variables (oil, gold, and silver) meanwhile and unlike many empirical studies, don’t we have found that oil doesn’t cause changes in precious metals prices. Therefore, the idea that Islamic financial markets provide diversification benefits and they are safe havens during oil crisis cannot be supported empirically.DOI: 10.15408/aiq.v10i2.7171